Mechanisms of Development and Variants of Therapeutic Management of Steroid Resistance in Patients with Atopic Dermatitis - Nikolay N. Murashkin; Roman V. Epishev; Alexander I. Materikin; Eduard T. Ambarchyan; Leonid A. Opryatin; Roman A. Ivanov ("Paediatrician" Publishers LLC, 2021)
Skin is the natural habitat for complex bacterial, fungal, and viral communities (ecosystems). The microbiome of such communities is always in close relationship with the host genome, and the development of these ecosystems happens under the effects of morpho-physiological and immunological characteristics of the skin (sebaceous glands concentration, humidity, and temperature) and environmental factors. Metagenomic studies have shown significant diversity in skin ecosystems. Moreover, the role of commensal microorganisms in skin immune response modulating to various agents and, thus, its correlation with skin diseases pathogenesis is no longer in doubt. New probiotic and antimicrobial agents for external treatment have been developed according to these knowledges.